Efficacy of current treatments against hepatitis C virus - Zepeda, Jose M.; Murrieta, Alejandro; Contreras, Javier; Osuna, Felix; Calderon, Luis Antonio Villalobos; Pérez, Miriam; Ramírez, María Holanda García; Dorantes, Omar De J. (International Journal of Basic & Clinical Pharmacology, 2022)
It is estimated that currently, in the world, approximately 3% of the population has chronic hepatitis, the hepatitis C virus is the etiological agent most related to the development of this pathology. The diversity of genotypes (7) and quasi-species of HCV, due to its high mutation rate, interferes with an effective humoral immunity. The aim of this work is precisely to evoke those usual drugs used in HCV therapy, as well as cutting-edge drugs. The goal of treatment is the eradication of HCV infection. One strategy offered by the WHO is to eradicate the virus in at-risk populations. Alternatives to the previously used treatment with interferon and ribavirin are shown in this paper; protease inhibitors and other targets have now been developed to make eradication of the virus more effective.